2011
DOI: 10.3109/01480545.2011.589440
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of erythropoietin against cisplatin-induced nephrotoxicity in rats: antigenotoxic and antiapoptotic effect

Abstract: Cisplatin (Cisp) is an active cytotoxic agent that was found efficient in the treatment of various types of solid tumors. Its nephrotoxic effect has been very well documented in clinical oncology. Erythropoietin (EPO), a renal cytokine-regulating hematopoiesis, has recently been shown to exert important cytoprotective effects in many experimental injuries. The aim of this study was to explore whether EPO would protect against Cisp-induced apoptosis in rat kidney. Adult Wistar rats were treated with saline solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Olgun et al [25] reported that rhEPO decreased hypoxic-ischemic encephalopathy-induced apoptotic cell death in the cochlea, spiral ganglion, and central auditory pathways of newborn rats and prevented hypoxic-ischemic encephalopathy-induced hearing loss. Rjiba-Touati et al [26] demonstrated that treatment with EPO decreased CDDP-induced apoptotic cell death and tubular injury in rat kidney. They also showed that the antiapoptotic action of EPO was more pronounced when administrated 24 hours before CDDP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Olgun et al [25] reported that rhEPO decreased hypoxic-ischemic encephalopathy-induced apoptotic cell death in the cochlea, spiral ganglion, and central auditory pathways of newborn rats and prevented hypoxic-ischemic encephalopathy-induced hearing loss. Rjiba-Touati et al [26] demonstrated that treatment with EPO decreased CDDP-induced apoptotic cell death and tubular injury in rat kidney. They also showed that the antiapoptotic action of EPO was more pronounced when administrated 24 hours before CDDP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that EPO ameliorates CP-induced nephrotoxicity [9, 10, 15, 2326], while female sex hormone, estrogen, inhibits EPO production in female rats [19] and decreases EPO gene expression during hypoxia [20]. Some evidence also has reported the sex difference response to CP-induced nephrotoxicity and renal function [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen decreases hypoxic induction of plasma EPO, and renal EPO gene expression is mediated by increasing NO production [20, 36], and NO can reduce EPO gene expression in kidneys [37]. EPO, as an antioxidant and antiapoptotic agent, has a protective effect against CP-induced nephrotoxicity [14, 23]. Recombinant human EPO reduces the serum levels of MDA and glutathione, induced by CP treatment [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that recombinant human erythropoietin administration especially in pretreatment condition protected rats against Cisplatin-induced renal oxidative stress and nephrotoxicity (39). In another study conducted by Rjiba-Touati et al to find the protective effect of erythropoietin against Cisplatin-induced apoptosis in rat kidney, a reduction of apoptosis by up regulation of antiapoptotic protein expressions, down regulation of pro apoptotic protein levels, and reduction of caspase-3 activity in male Wistar rats was seen (40). Hence it seems that the protective action of Eprex on the kidney probably is not directly related to its hematopoietic effects (14).…”
Section: Discussionmentioning
confidence: 99%